GUILLAUME APOLLINAIRE ȘI PLEDOARIA „SPIRITULUI NOU” ÎN LITERATURĂ: O RECAPITULARE - PILCHIN, magistru în filologie, Universitatea de Stat din Moldova, Chișinău, Ivan (BIBLIOPOLIS, 2020)
Starting from the essay by G. Apollinaire „The new spirit and poets” this article seeks to follow an algorithm of affirmation and fixing of a new aesthetic, the transition to a new poetic consciousness. It also refers to the poetic texts by G. Apollinaire that present a decisive moment which opens a new era and impose the necessity of a „new human” according to it. G. Apollinaire argues for a new poetic spirit which is, in essence, „the spirit of the age in which we live”, an age „full of surprising things”. He argues for a „new realism”, the authenticity and credibility of poetic representations, their simplicity, and their ability to surprise.